Brandon/Hill selected list of print books and journals in allied health - Hill, Dorothy R. (Medical Library Association, 2000)
This list of 424 books and 77 journals is intended as a selection guide for print literature to be used in a library supporting allied health educational programs or allied health personnel in either an academic or health care setting. Because of the impossibility of covering the large number and wide variety of allied health professions and occupations, the recommended publications are focused primarily on the educational programs listed and recognized by the American Medical Association and other accrediting bodies. Books and journals are categorized by subject; the book list is followed by an author/editor index, and the subject list of journals by an alphabetical title listing. Items suggested for initial purchase (167 books and 31 journals) are indicated by asterisks. To purchase the entire collection of books and journals (2000 subscriptions) would require an expenditure of about $31,970. The cost of only the asterisked items totals $12,515.